nofia Metode Demonstrasi Berbasis Teknik Shaping Dapat Meningkatkan Keterampilan Mencuci Baju Pada Anak Tunagrahita Kategori Sedang - Wahyuni, Nofia Sri (journal of residu, 2019)
This research is motivated by problems found in class VII SLB Bina Bangsa in mentally retarded students      from January to March 2019. Researchers found a student who had not been able to wash clothes properly. This study aims to determine whether the method of demonstration based on shaping techniques can improve clothes washing skills. This study uses a class action research method consisting of two cycles, each cycle consisting of planning, action, observation and reflection. The results of the study in the initial conditions were 24%. After carrying out the first cycle the results of the acquisition of an average value of 38%, the results of the second cycle of the acquisition of an average value of 62%. These results indicate that the method of demonstration based on shaping techniques can improve clothes washing skills in mentally retarded students of the moderate category. From these results it can be seen that the demonstration method based on shaping techniques can improve clothes washing skills.